A Model to Evaluate Variables Impacting the Productivity of Software Maintenance Projects - Banker, Rajiv D.; Datar, Srikant M.; Kemerer, Chris F. (Management Science, 1991)
The cost of maintaining application software has been rapidly escalating, and is currently estimated to comprise from 50–80% of corporate information systems department budgets. In this research we develop an estimable production frontier model of software maintenance, using a new methodology that allows the simultaneous estimation of both the production frontier and the effects of several productivity factors. Our model allows deviations on both sides of the estimated frontier to reflect the impact of both production inefficiencies and random effects such as measurement errors. The model is then estimated using an empirical dataset of 65 software maintenance projects from a large commercial bank. The insights obtained from the estimation results are found to be quite consistent for reasonable variations in the specification of the model. Estimates of the marginal impacts of all of the included productivity factors are obtained to aid managers in improving productivity in software maintenance.